Sexuality and intimacy in ALS: systematic literature review and future perspectives. Issue 6 (11th December 2018) - Poletti, Barbara; Carelli, Laura; Solca, Federica; Pezzati, Rita; Faini, Andrea; Ticozzi, Nicola; Mitsumoto, Hiroshi; Silani, Vincenzo
Abstract : Several features of amyotrophic lateral sclerosis (ALS) impact on sexuality and intimate relationship; however, the issue has received poor attention so far. We performed a systematic literature review in order to provide an up-to-date account of sexuality in ALS. References were identified by searches of PubMed, Web of Science, Scopus and PsycINFO (1970–2017, English literature). The following were the key terms: 'sexual' OR 'sexuality' OR 'intimacy' OR 'marital' AND 'ALS' OR 'Amyotrophic Lateral Sclerosis' OR 'Motor Neuron Disease' OR 'MND'. Titles and abstracts were screened for relevance and a full-text analysis was performed on the selected articles. Studies were included if they referred to sexual well-being/activities/functions or intimate relationship between patients and their partners and management of such topic by clinicians. Eligibility assessment was performed independently by two reviewers. A thematic and level of evidence classification of studies was performed. Studies' design, objectives, measurements and outcomes were summarised. Thirty articles were included and four topics were identified: intimacy in the dyads; sexual activities in patients and with their partners; sexual function disturbances; and sexuality and cognitive-behavioural alterations. The quality of the studies varies, with globally poor level of evidence. Some sexuality issues have been only sparsely addressed, such as gender-related differences, same-sex relationships and sexual activities other than intercourse. Sexuality in ALS is still not adequately considered by clinicians and researchers. We present preliminary recommendations for improving sexuality and intimacy at any ALS multidisciplinary clinics.